Pengaruh Model Pembelajaran Realistic Mathematic Education Berbasis Etnomatematika Madura Terhadap Kemampuan Literasi Matematika Siswa - Naila Nur Rozalia; Umi Hanik; Nike Ika Nuzula (Populer: Jurnal Penelitian Mahasiswa, 2024)
The purpose of this study is to ascertain how fourth grade students at SDN Keleyan 2 are impacted in terms of their mathematical literacy by realistic math instruction grounded in Madurese ethnomathematics. This is a quantitative study using an experimental research design; a quasi-experimental design and a nonequivalent control group design are the types of research designs employed. 48 SDN Keleyan 2 class IV students served as samples. Classes experimental and control were employed in this study. In this study, tests of mathematical literacy and observation were used as data gathering methods. The data analysis includes an independent sample t-test for hypothesis testing, homogeneity testing, and a prerequisite test utilizing the normality test. Ho is rejected and Ha is approved based on the findings of the independent sample t-test data analysis, which showed that t-test = 7,757 > t-table = 2,012. As a result, it was determined that fourth grade pupils at SDN Keleyan 2 had significantly higher mathematical literacy levels when the model realistic mathematic education learning based on Madurese ethnomathematics was applied.